(untitled) (ModaPalavra e-periódico, 2015)
This reflection is part of recent interdisciplinary doctoral research about the imagery, narrative and discursive production of conservative whiteness in the high fashion journal pages and ready-to-wear luxury Vogue Brazil. Theoretical and methodological issues included notably in the fields of cultural studies, gender and postcolonial are articulated through a qualitative analysis of two fashion editorials, published in 2007 and 2008 and pointed to the "self-exoticism" of nature and Brazilian popular culture -symbolically marked by the primacy of the body [white] women, considering also the legitimacy of producing voices speeches of competence and constant renewal, and the intersection of racial symbolic violence with other forms of domination (class and gender / sexual).